Sistem Pakar Pemilihan Sepeda Motor Dengan Metode Simple Additive Weighting - Rahmawati, Desi Nur, Dr. Heru Supriyono, M.Sc (2015)
Motorcycle is an inexpensive means of transportation and is fairly easy to operate and much-loved by the public because many motorcycle models with different variants and specifications of the motor that makes the consumer confusion in selecting the desired krieteria . In this research is to facilitate the consumer in choosing motorcycles of various models of motorcycles . SAW will be implemented on a web -based system that can be accessed via online using a web browser or mobile phone . In making the application with a simple additive weighting method , testing is done by using the data questionnaire which was distributed to the public . And the results of the testing concluded that 80% of the public agreed that future applications used in facilitating the election of a motorcycle .